Pekanbaru Convention Center Dengan Pendekatan Arsitektur Melayu - Ramadani Ramadani; Wahyu Hidayat; Andre Novan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Pekanbaru as the capital of Riau province has potential in the development of economy and tourism industry. Economic development leads to new discoveries, exchanges and dissemination of information, resulting in universal meeting activities such as seminars, conventions and exhibitions. Convention Center is a building to conduct convention and exhibition activities with a large capacity. The Convention Center is designed with Malay architectural approach, this is because malay people always gathering and meeting on the building called the balai house. One of the balai houses in Pekanbaru which became the custom house of Riau province is Selaso Jatuh Kembar. By using Malay architecture as a design approach, then come the concept of Harmony Social which means harmony on the sociality. Harmony Social is the harmony of social character / socialization with the house of Selaso Jatuh Kembar. The concept is applied by transforming the Selaso Jatuh Kembar house. The results of transformation include the order of mass, mass formation, facade, landscape, and color.Keywords: Convention Center, Malay Architecture, Transformation